2016
DOI: 10.2147/vhrm.s119646
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship of cardioankle vascular index with BMI in healthy Japanese subjects: a cross-sectional study

Abstract: ObjectiveThe objective of this study is to investigate the association of body mass index (BMI) with arterial stiffness assessed by cardioankle vascular index (CAVI).Subjects and methodsA retrospective cross-sectional study was conducted in 23,257 healthy Japanese subjects (12,729 men and 10,528 women, aged 47.1 ± 12.5 years, BMI 22.9 ± 3.4 kg/m2) who underwent health screening between 2004 and 2006 in Japan. Exclusion criteria were current medication use and a past history of cardiovascular disease, hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 71 publications
10
39
1
11
Order By: Relevance
“…In addition, we have found a negative correlation between BMI and CAVI in the overall population and in both genders. Nagayama et al found that an inverse correlation between BMI and CAVI in healthy middle-aged subjects, and they hypothesized that systemic accumulation of adipose tissue, per se, leads to reduced arterial stiffness [ 44 ]. In another study of middle-aged and elderly Chinese subjects, an inverse correlation between BMI and CAVI was also observed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have found a negative correlation between BMI and CAVI in the overall population and in both genders. Nagayama et al found that an inverse correlation between BMI and CAVI in healthy middle-aged subjects, and they hypothesized that systemic accumulation of adipose tissue, per se, leads to reduced arterial stiffness [ 44 ]. In another study of middle-aged and elderly Chinese subjects, an inverse correlation between BMI and CAVI was also observed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study of middle-aged and elderly Chinese subjects, an inverse correlation between BMI and CAVI was also observed [ 21 ]. It seems that high BMI values do not always mean high arterial stiffness, which is probably related to the distribution of body fat, as the absolute amount of adipose tissue does not increase the risk of cardiovascular disease in many overweight people [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…tionship between CAVI and BMI in healthy individuals with a mean age of 47.1 years 50) . Other investigators have also reported a similar inverse relationship between CAVI and BMI in 2,354 adults ranging in age from 35 to 74 years, with a mean age of 61.4 years 51) .…”
Section: General Obesitymentioning
confidence: 99%
“…Since PWV is known to be associated with blood pressure, CAVI has been developed to measure arterial stiffness, and the measurement is basically independent of blood pressure. In a recent study, however, CAVI is inversely associated with the BMI of both male and female 35) . This association is consistent with our findings, although the reason is still uncertain.…”
Section: Cavi Cavimentioning
confidence: 76%